Metaphors in the Tibetan Explanatory Tantra - Sabernig, Katharina (Religions, 2019)
The development of medical theories and concepts is not isolated from the societal "Zeitgeist" of any medical culture. Depending on the purpose and the audience addressed, different metaphors are used to explain different medical content. Doubtlessly, Tibetan medicine is associated with Tibetan Buddhism and various medical topics are linked to Buddhist knowledge. In addition to the religious link, medical texts and terms also make use of nomadic or even military metaphor. In anatomical language, metaphor and metonym are usually based on visual or morphological similarities. In the case of physiological, pathological, or therapeutic processes, metaphor often deals with dynamic and strategic elements drawn from comparisons with everyday life and other spheres of activity. These models commonly relate to specific historical and cultural backgrounds. Let us think of the European "body republic" in Renaissance medical theory or the theory of the "cell state" devised by Rudolf Virchow (1821-1902), which explains the concept of cellular pathology. Asian examples that use state functions as metaphors for the hierarchy of internal organs in Chinese and Tibetan medicine are well-known. In addition to these prominent state models, Tibetan medical language and its visual representation is rich in metaphor. In this preliminary paper not all occurring metaphors can be discussed in depth, however different types of Tibetan medical metaphor will be compared and contextualized with non-Tibetan metaphors from other contemporary and historical medical cultures.